2022
DOI: 10.1177/26323524211070569
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of using moxibustion and or acupuncture for cancer-related insomnia: a systematic review and meta-analysis of randomised controlled trials

Abstract: Introduction: This study aimed to synthesise the best available evidence on the safety and efficacy of using moxibustion and/or acupuncture to manage cancer-related insomnia (CRI). Methods: The PRISMA framework guided the review. Nine databases were searched from its inception to July 2020, published in English or Chinese. Randomised clinical trials (RCTs) of moxibustion and or acupuncture for the treatment of CRI were selected for inclusion. Methodological quality was assessed using the method suggested by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(161 reference statements)
1
5
0
Order By: Relevance
“…These results offer promise as they underscore a potentially viable approach to managing and treating fatigue and associated symptoms among cancer survivors. These results align well with a growing body of literature demonstrating the ability of acupuncture and moxibustion to help alleviate the fatigue [26,27] and insomnia [28,29] experienced by patients diagnosed with or recovering from cancer. Strikingly, ILM failed to significantly improve fatigue as compared to sham treatment at the end of the treatment interval despite exhibiting significant benefits at later follow-up time points, consistent with the results of another recent moxibustion trial [27].…”
Section: Discussionsupporting
confidence: 86%
“…These results offer promise as they underscore a potentially viable approach to managing and treating fatigue and associated symptoms among cancer survivors. These results align well with a growing body of literature demonstrating the ability of acupuncture and moxibustion to help alleviate the fatigue [26,27] and insomnia [28,29] experienced by patients diagnosed with or recovering from cancer. Strikingly, ILM failed to significantly improve fatigue as compared to sham treatment at the end of the treatment interval despite exhibiting significant benefits at later follow-up time points, consistent with the results of another recent moxibustion trial [27].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that auricular acupuncture (AA) ( 9 ), scalp acupuncture (SA) ( 10 ), electro-acupuncture (EA) ( 11 ), and intradermal needling (IN) ( 12 ) might be more advantageous in treating CRI than WM, placebo-sham acupuncture (PSA), or routine care (RC). A systematic review ( 13 ) published in 2022 found that acupuncture and/or moxibustion have an affirmative effect on the treatment of CRI. Such treatment could be considered an adjuvant alternative to current CRI management.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with previous meta-analyses (19,20,(24)(25)(26), this study carried out a more comprehensive retrieval, including more recently published trials, successfully updating the evidence. The previous meta-analysis encompassed some studies in which participants were not diagnosed with CRI, PSQI served merely as a secondary outcome, and the experimental groups included other non-pharmaceutical interventions.…”
Section: Discussionmentioning
confidence: 99%